GAYA HIDUP SHOPAHOLIC PADA MAHASISWA (STUDI PADA MAHASISWA FISIP UNIVERSITAS RIAU YANG KECANDUAN BERBELANJA PAKAIAN) - Nurul Arbaini; Yonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
According to Boudrillad (2004), there is a tendency in the community to do consumption or buying something not because the value of advantages, but because the lifestyle. Consumtive behavior only intended for people who like to purchase goods without care to the its advantages. This is a phenomenon that occurs on student of social and political science faculty at the RiauUniversity. But, on the other hand this behaviour has a function for survival like the ability to keep the existence of students in the their community. Life style on social and political science student at this time shows the lifestyle that the shopaholic, so that it can be categorized into several typologies of shopaholic. The purpose of this research is to find out students who haveshopaholic lifestyles which seen from the student's profile and to find out the dominant typology of shopaholic that occurred among students of social and political science faculty. The method in this research is descriptive qualitative, by using the technique of accidental sampling, interviews, observation and documentation.The results of this research show that students of social and political science faculty at theRiau University haveshopaholic lifestyle mostly come from students who live at the boardinghouse as well as earn money monthly from their parents. The cause of Shopaholic lifestyle on students is the willingnesstokeep their existence in social environment. The typology of shopaholic onstudents of social and political science faculty at the RiauUniversity is compulsive shopaholic, where they become a shopaholic because want tokeep their existence and because most of students were bored in study and othersactivitiesat the campus.Keywords: Lifestyle, Shopaholic,Consumtive